Quirópteros como hospedeiros do fungo Coccidioides posadasii : descrição do primeiro registro de isolamento - Silva, Kylvia Rocha de Castro e (2011)
The order Chiroptera is shown as a reservoir for various infectious agents, including protozoan, bacteria, virus and fungi. To investigate the eco-epidemiological aspects of Histoplasma capsulatum in Northeast Brazil, 83 bats were captured in urban and rural areas in Ceará, collected in day and night, during the period August 2010 to March 2011. After euthanasia, fragments of sleen, liver and lung were removed, macerated and 100 μL aliquots were plated on agar containing modified BHI, which were incubated for up to six weeks at temperatures of 28 ºC and 35 ºC. Aliquots of each remaing macerated material stored at -20 °C. Although the fungus was not isolated in any samples, after 21 days at 35 ºC was observed the growth of a fungal colony suggestive of Coccidioides spp. in lung samples of the species Carollia perspicillata. Fragments of the bet lung removed from storage at -20 ºC and analyzed by optical microscopy revealed spherical structures similar to the shape of the parasitic fungus. The colonies were investigated by means of the reversion in vivo in a murine model, with observation of the animals incoculated up to four weeks. The molecular identification of cultures was performed by PCR specific for C. posadasii, using the oligonucleotides Coi9-R and Coi9-F. Finally, samples of macerated lung, spleen and liver were investigated for the presence of antibodies or antigens specific for C. posadasii, as well as the presence of anti-Histoplasma, by immunodiffusion. Spherules of Coccidioides spp. features were visualized in lung samples of mice experimentally infected. Molecular analysis of cultures isolated from lungs of C. perpicillata, as well as organs of mice, showed approximately 630 pb band, characteristic of C. posadasii. By immunodiffusion reaction, two animals were detected reagents for Coccidioides antigens. The animals belonged to the species Glossophaga soricina and Desmodus rotundus and an animal of the species G. soricina antibody-positive for Coccidioides. There was no presence of anti-Histoplasma is any sample. The present study shows the first isolation of C. posadasii in bats. Additionally, in an unprecedented manner, we detected antigens and antibodies specific to C. posadasii these animals. Its is necessary to the study of bats in ecoepidemiology the pathogen.